Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content1. The role of strategic thinking in achieving government innovation: A filed study on employees of the Ministry of Justice in JeddahMrs. Seham Sharaf Alzhrani, Co-Prof. Faisal Ahmad Shuaibi2. The impact of implementing the health transformation strategy on service delivery from the employees' point of view in KSAMr. Hassan Amer Al-Shehri3. The impact of empowerment of women leaders on job performance: An empirical study on the government sector in KSACo-Prof.  Hossam Hassan Sharawi, Ms. Amani Saleh Al-Said4. The Use of Information Technology and its Impact on The Efficiency of Modern Management Accounting Methods in Jordanian Government Institutions in the Time Period 2022-2023Mr. Majdi Mohammad Ahmad Almalkawi5. The effectiveness of procedures followed by organizers during Hajj season on the safety of the elderly in Al-Mashaer train areaMrs. Lina Mohammed Alsulimani6. Factors affecting the quality of internal audit reports in Jordanian ministries and government institutionsMr. Malik Hussein Ahmad Almalkawi7. Modern digitization and its expected impact on the efficiency of Islamic financial transactions in LibyaMrs. Hamida Abdel Aziz Ali Islio, Dr. Muhammad Ahmed Ali Dabou8. Modern methods of the crime of terrorism in domestic and international lawsLecturer \ Amnah Mulfi Alsulami
Keywords: Journal of Economic, Administrative and Legal Sciences